The Effect of Light Rail Transit on Physical Activity: Design and Methods of the Travel-Related Activity in Neighborhoods Study - Durand, Casey P.; Oluyomi, Abiodun O.; Gabriel, Kelley Pettee; Salvo, Deborah; Sener, Ipek N.; Hoelscher, Deanna M.; Knell, Gregory; Tang, Xiaohui; Porter, Anna K.; Robertson, Michael C.; Kohl, Harold W. (Frontiers in Public Health, 2016)
Background: Use of mass transit has been proposed as a way to incorporate regular physical activity into daily life because transit use typically requires additional travel to access and depart the stop or station. If this additional travel is active, a small but potentially important amount of physical activity can be achieved daily. Although prior research has shown that transit use is associated with physical activity, important questions remain. Utilizing a major expansion of the Houston, Texas light rail system as a natural experiment, the Houston TRAIN Study was developed to address these unanswered questions. Purpose: The purpose of the TRAIN Study is to determine if the development of light rail lines in Houston, Texas will prospectively affect both transit use and physical activity over four years. We also aim to understand how contextual effects (i.e. moderators or interaction effects), such as the neighborhood built environment and socioeconomic factors, affect the primary relations under study. Methods: The TRAIN Study is a longitudinal cohort design, in which participants are recruited at baseline from a 3-mile buffer around each of the three new lines and measured annually four times. Recruitment is accomplished via telephone contact, ads in newspapers and advertising circulars, and targeted community outreach. Data are collected via mail and include: questionnaire-assessed factors such as perceived neighborhood characteristics, attitudes about transportation, demographics, and reported physical activity; a travel diary; and accelerometry. Additionally, field-based neighborhood audits are conducted to capture micro-scale environmental features. To assess macro-scale environmental characteristics, we utilize GIS mapping and spatial analyses. Statistical analyses will be conducted using latent growth curve modeling and discrete choice models, with a focus on identifying moderating factors (i.e. statistical interaction effects). Selection bias will be controlled via propensity score analysis. Conclusion: The TRAIN study is a unique opportunity to study how a multi-billion dollar investment in mass transit can simultaneously affect transportation needs and physical activity behavior. This comprehensive evaluation will provide needed evidence for policy makers, and can inform health impact assessments of future transportation projects around the world.